Optimizing Madrasah Quality: A Strategic Approach to Human Resource Management - Fathurrahman, Fathurrahman; Fitriyah, Lailatul; Aini, Tsamar Nur; Adeoye, Moses Adeleke; Hakim, Ahmad Muzakki (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research analyzes human resource (HR) development strategies and their implications for quality management at Madrasah Aliyah Negeri (MAN) 1 Probolinggo. This research uses a qualitative case study type approach. Data collection techniques are carried out through observation, interviews, and documentation. The data analysis technique is carried out in stages, from data presentation to data reduction and conclusion. The research results show that implementing a comprehensive HR development strategy at MAN 1 Probolinggo can strengthen its commitment to creating a dynamic and adaptive educational environment. This strategy is designed to respond rapidly to changes in education and society and emphasizes improving the quality of education as the primary mission. This research provides implications regarding strategic human resource management strategies that can improve the performance of madrasas in providing quality educational services. By focusing on human resource development, madrasas can strengthen their long-term commitment to improving the quality of education.